2021
DOI: 10.3390/ijms22020758
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Tomato TPR Gene Family

Abstract: Tomato (Solanum lycopersicum) as an important vegetable grown around the world is threatened by many diseases, which seriously affects its yield. Therefore, studying the interaction between tomato and pathogenic bacteria is biologically and economically important. The TPR (Tetratricopeptide repeat) gene family is a class of genes containing TPR conserved motifs, which are widely involved in cell cycle regulation, gene expression, protein degradation and other biological processes. The functions of TPR gene in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Therefore, it is hypothesized that DGL1 can improve the stability of plant cells in an adversarial environment by inducing the expression of genes during the plant response to thermal stimulation. Meanwhile, DGL1 upregulated the expression of TPR-encoding genes, and TPR proteins have important roles in cell cycle regulation, stress response, gene expression, protein degradation, and other biological processes (Zhou et al, 2022 ). Lin et al ( 2013 ) found that the AtTPR1 gene was involved in regulating the growth hormone uptake process in Arabidopsis .…”
Section: Results and Analysismentioning
confidence: 99%
“…Therefore, it is hypothesized that DGL1 can improve the stability of plant cells in an adversarial environment by inducing the expression of genes during the plant response to thermal stimulation. Meanwhile, DGL1 upregulated the expression of TPR-encoding genes, and TPR proteins have important roles in cell cycle regulation, stress response, gene expression, protein degradation, and other biological processes (Zhou et al, 2022 ). Lin et al ( 2013 ) found that the AtTPR1 gene was involved in regulating the growth hormone uptake process in Arabidopsis .…”
Section: Results and Analysismentioning
confidence: 99%
“…This gene encodes a tetratricopeptide repeat (TPR)-like superfamily protein, which is involved in the regulation of different cellular functions [ 32 , 33 ]. In tomatoes, TPR family genes were previously reported to respond to various biotic and abiotic stresses [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…These TPR domain‐containing proteins are part of multisubunit protein complexes that regulate transcription, transport, photosynthesis of the photosynthetic system, and protein folding and perform diverse functions during plant development and drought stress (Wei & Han, 2017). In tomatoes, for example, TPR family genes have been reported to respond to various biotic and abiotic stresses (Zhou et al., 2021).…”
Section: Discussionmentioning
confidence: 99%